ERSEPSI KEADILAN ORGANISASIONAL PEGAWAI NEGERI SIPIL DI KABUPATEN TANGGAMUS PROVINSI LAMPUNG - Zainnur M Rusdi; Dina Safitri (Jurnal Manajemen Sinergi, 2014)
Employment institution that promotes the principles of organizational justice willsurely make the employees into the spirit to work because it will lead to thewelfare of its employees. As in the case of salary, if the employment institutionsprovide appropriate salary to the employees it will give a good perception of thefairness of the agency policy. Conversely, if the agency does not provide salarybased on workload, skill and ability of employees and other matters set forth inthe agency, it will give the negative perception of fairness.Civil servants are state officials in the service of the community to provideequitable services to various public sector. Civil servants are required to carryout their duties responsibly and professionally so as to ensure the implementation of public service that is clean and professional. It certainly would be realized if the employee can feel the organizational justice in the agency where he worked both in terms of salary, participation in decision-making, and in terms of good treatment from the superiors without discrimination.Based on the results of the descriptive analysis using the obtained mean thatprocedural justice is the dominant justice felt by employees (mean = 21.92), while the interactional justice (mean = 15.45) and distributive justice (mean = 11.28) still needs to be improved. Procedural fairness can be improved further by providing opportunities for employees to apply for aspiration or objection andparticipate in decision making. The treatments were friendly and attentive bysuperiors to employees can improve perceptions of interactional justice. Inaddition, the organization also must ensure fair treatment and decent in terms of remuneration to be adapted to the workload and employee experience.